Analysis of Factors Affecting Employee Work Productivity at Lovindra Madiun Travel Transportation Service - Maymuna Harum Iswantami; Ely Masykuroh (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Lovindra Travel has a total workforce of approximately 49 workers who are positioned in accordance with their respective expert fields. Lovindra Travel is considered to be less than reaching the target in increasing its work productivity. The management has provided high compensation, placing employees in positions that are in accordance with their respective expertise, the company also provides a fairly good work environment facilities. However, based on the field, many employees arrived late and did not pick up customers on time. The data analysis techniques used are validity, reliability, classical assumption tests and multiple linear regression tests consisting of t tests and f tests. The results of the partial t-test study showed that the work environment had a significant effect of 0.004 on employee work productivity, skills had a significant effect on productivity by 0.027 while compensation also affected employee work productivity by 0.043. In test F simultaneously, all three variables affect employee work productivity by 0.000.